Odmerki mineralov in vitaminov - Peterlin-Mašič, Lucija (Farmacevtski vestnik, 2020)
The European Food Safety Authority (EFSA) and the National Institute of Public Health (NIJZ in accordance with the DACH guidelines) provide a number of dietary reference values (DRVs) for minerals and vitamins intake. In the manuscript are presented various dietary reference values, what they mean, how they are used and who should use them. The labelling of minerals and vitamins on foods and tolerable upper intake levels for vitamins and minerals are also presented. In addition, risk assessment of using products with high daily doses of vitamin D and vitamin C are described. The needs for minerals and vitamins vary from person to person and from day to day. Recommendations (according to DACH recommendations) or population reference intakes (according to EFSA recommendations) by definition cover the needs of almost all (97.5%) persons within the group of healthy individuals. For an individual, only the intake that covers the needs for a particular vitamin or mineral is recommended. With a daily intake of a balanced and varied diet, it is unlikely that the supply would be too low.
Keywords: Minerali; Prehranska dopolnila; prehranske referenčne vrednosti; priporočeni dnevni vnosi; Vitamini; zgornja sprejemljiva meja vnosa